HMGB1 is a Potential Mediator of Astrocytic TLR4 Signaling Activation following Acute and Chronic Focal Cerebral Ischemia. (20th February 2020) - Famakin, Bolanle M.; Tsymbalyuk, Orest; Tsymbalyuk, Natalia; Ivanova, Svetlana; Woo, Seung Kyoon; Kwon, Min Seong; Gerzanich, Volodymyr; Simard, J. Marc
Abstract : Limited, and underutilized, therapeutic options for acute stroke require new approaches to treatment. One such potential approach involves better understanding of innate immune response to brain injury such as acute focal cerebral ischemia. This includes understanding the temporal profile, and specificity, of Toll-like receptor 4 (TLR4) signaling in brain cell types, such as astrocytes, following focal cerebral ischemia. This study evaluated TLR4 signaling, and downstream mediators, in astrocytes, during acute and chronic phases post transient middle cerebral artery occlusion (MCAO). We also determined whether high mobility group box 1 (HMGB1), an endogenous TLR4 ligand, was sufficient to induce TLR4 signaling activation in astrocytes in vivo and in vitro. We injected HMGB1 into normal cortex, in vivo, and stimulated cultured astrocytes with HMGB1, in vitro, and determined TLR4, and downstream mediator, expression by immunohistochemistry. We found that expression of TLR4, and downstream mediators, such as inducible nitric oxide synthase (iNOS), occurs in penumbral astrocytes in acute and chronic phases after focal cerebral ischemia, but was undetectable in cortical astrocytes in the contralateral hemisphere. In addition, cortical injection of recombinant HMGB1 led to a trend towards an almost 2-fold increase in TLR4 expression in astrocytes surrounding the injection site. Consistent with these results, in vitro stimulation of the DI TNC1 astrocyte cell line, with recombinant HMGB1, led to increased TLR4 and iNOS message levels. These findings suggest that HMGB1, an endogenous TLR4 ligand, is an important physiological ligand for TLR4 signaling activation, in penumbral astrocytes, following acute and chronic ischemia and HMGB1 amplifies TLR4 signaling in astrocytes.